2016
DOI: 10.1002/anie.201602569
|View full text |Cite
|
Sign up to set email alerts
|

NH‐Heterocyclic Aryliodonium Salts and their Selective Conversion into N1‐Aryl‐5‐iodoimidazoles

Abstract: Abstract:The synthesis of N-arylimidazoles substituted at the sterically encumbered 5 position is a challenge for modern synthetic approaches. Here we report a new family of imidazolyl aryliodonium salts that serve as stepping stones on route to the selective formation of N1-aryl-5-iodoimidazoles; the iodine can now act as a "universal" placeholder to be transformed into further substituents. These new λ 3 -iodanes are produced by treating the NH-imidazole with ArI(OAc)2, and are converted to N1-aryl-5-iodoimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 50 publications
9
32
0
Order By: Relevance
“…Ap reliminary investigation also revealed that the coordination of N-Me-benzimidazole to the Cu I center may disfavor the binding of two molecule of 3 to the same copper center, hence enforcing an intramolecular phenyl transfer. [21] In agreement with Scheme 5, the preformed zwitterionic 3 was also an excellent substrate even in the absence of abase [Eq. (1)].…”
Section: Angewandte Chemiesupporting
confidence: 58%
“…Ap reliminary investigation also revealed that the coordination of N-Me-benzimidazole to the Cu I center may disfavor the binding of two molecule of 3 to the same copper center, hence enforcing an intramolecular phenyl transfer. [21] In agreement with Scheme 5, the preformed zwitterionic 3 was also an excellent substrate even in the absence of abase [Eq. (1)].…”
Section: Angewandte Chemiesupporting
confidence: 58%
“…The competition between ligand coupling and aryne formation in arylations of hydroxide with diaryliodonium salts 1 a , 1 c , and 1 d was studied by DFT calculations using two different functionals (B3LYP‐D3, M06‐2X) commonly used for hypervalent iodine reactions . We started to investigate the reaction between 1 d and hydroxide in CH 2 Cl 2 (Figure ) .…”
Section: Resultsmentioning
confidence: 99%
“…The SDD basis set with an applied effective core potential (MWB46) was used for iodine, Pople's triple‐zeta basis set with added polarization and diffuse functions (6–311+G(d,p)) were used for N, O, F, Cl and Na atoms while the triple‐zeta basis set with added polarization (6–311G(d,p)) were used for the H , C and S atoms. Several iodine(III) reactions have recently been studied by DFT using similar setups . The systems were studied in both CH 2 Cl 2 and H 2 O using the polarizable continuum model (PCM, Surface=SES, Radii=UFF), and the results in H 2 O are given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…A different approach towards the functionalisation of heterocycles was taken by Shafir, Lledós, and co-workers, who investigated the intrinsic conversion of novel N-heterocyclic aryliodonium salts 1b [ 35 ]. Under the influence of base, copper catalyst and N -Me-benzimidazole as a ligand, the heterocyclic aryliodonium salt 1b was converted into the N 1-aryl-5-iodoimidazole 18 as the major isomer ( Scheme 10 ).…”
Section: Reviewmentioning
confidence: 99%